Electric Field‐Enhanced Solid‐State Conversion of Ceramic Sr5(PO4)3F to Crystals. Issue 11 (28th July 2016) - Liu, Yin; Wu, Yiquan
Abstract : The single crystal solid‐state conversion of fluorapatite‐type Sr5 (PO4 )3 F (Sr‐FAP) has been achieved by spark plasma sintering with the assistance of NaF additive. NaF was determined to act as both a sintering aid and impurity solute along the grain boundaries (GBs), controlling both the space charge and GB migration rate. Postsintering isothermal annealing was performed to examine the effect of DC electric field on grain growth. From the space charge potential determined from impedance spectra measurements, in combination with the theoretical contribution of space charge to grain‐boundary energy reduction, it was concluded that the magnitude of the space charge in Sr‐FAP is temperature dependent. As such, a moderate decrease in polycrystalline GB driving force is the main cause for the increased single crystal migration length that was observed in this study.